Deconstrucción y reconstrucción de la identidad cultural europea. Ilustración, Romanticismo y Posmodernismo (2007)
The objective of this article is to describe the concept of European cultural identity derived from the postmodern deconstructionist vision. The study tracks the origins of this line of thinking to theideas of the Enlightenment and the romanticism, discussing its anti-metaphysical component whichmakes it refuse any substantial idea of a European cultural identity. Additionally, it offers an analysisof the "ideology of the difference" that supports this theoretical-cultural statement, with its transfer tothe dominant cultural-political discourse in the current integration process within the "New Europe".Contradicting this line of argumentation, the classical (Greco-Roman) and Christian origins are suggestedas historical-axiological roots of an authentic European identity and as the foundation to overcome thespiritual and cultural decay suffered now by the "Old Europe".